Implementasi Teori Andragogi dalam Meningkatkan Efektivitas Pembelajaran Orang Dewasa: Suatu Kajian Literatur - Nur Alia; Nurzamsinar Nurzamsinar; Sudirman Sudirman (JPPI (Jurnal Pendidikan Islam Pendekatan Interdisipliner), 2025)
This study aims to examine the theory of andragogical learning and its implications in adult learning processes. The research employs a qualitative approach with a library research method. Data were collected from various literature sources such as books, academic journals, and related documents discussing andragogy and adult education concepts. The results indicate that andragogical learning emphasizes learners’ experiences, needs, and independence. This theory views adult learners as active, self-directed individuals with strong intrinsic motivation to learn. The implementation of learning methods such as group discussions, case studies, simulations, and experiential learning has proven effective in enhancing learners’ understanding and participation. However, several challenges were identified, including differences in learners’ backgrounds, time constraints, and facilitator competence. Therefore, flexible, participatory, and needs-based learning strategies are required. In conclusion, andragogy can serve as an effective approach to improving the quality of adult education.